A modal for better authentication using hybrid biometrics by adding a side face with an ear - Kumar, Girish; Khushwaha, Dr. Ajay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Customer support in digital environment is most important by facilitating secure authentication and verification for both customer and retail stores. Ear and side face as hybrid biometric is effective and efficient method for authentication and recognition in biometrics. Many researchers reported that ear can be a biometric trait and has sufficient potential to be considered as biometric characteristic and same for the face it has been proved. In this research paper we investigated, with help of MATLAB tool. Idea of multiple traits of ear and side face biometric technique in retail stores for authorization and identification of customers in digital environment which is need of today.